Open Science in Peril: What is that new Open Science game? - Sundsbø, Katrine; Coyne, Aisling; Coombs, Sarah (Septentrio Conference Series, 2023)
Join us for the launch of a new open science quiz game - Open Science in Peril, where teams will compete against each other to find the questions to the answers we all have... Or do we? In this session, you can test your open science knowledge in a fun, engaging and social way. Or perhaps, you will learn a few new questions you didn’t know you had the answer to? Bring your smartypants and thinking cap, you’ll be assigned a team when you join the session, where four teams will play against each other to win enough money to cover the APC of your article. Will you be able to publish, or will you end up having to withdraw your article due to lack of funds?